Analisis Analisis Pengaruh Biaya Operasional dan Faktor Ekonomi terhadap Pola Operasi Pembangkitan pada Sistem Kelistrikan di Pulau Lombok - Nyoman Satriyadi Rai; Transna Putra Urip (Universitas Cenderawasih, 2023)
This study aims to determine the effect of operational costs and economic factors on generation operation patterns in the electrical system on Lombok Island. This research uses associative research methods. The sample in this study was 67 people. Which instrumentused in research, namely a questionnaire. The data were analyzed usingmultiple regression with the help of the SPSS program. The research results conclude.that the partial test results obtained indicate that the variable operational costs has a value of tcount (3.342)> ttable (1.669) and a significance value of (0.000) <0.05. This shows that operational costs (X1) have a significant and positive effect on generational operation patterns (Y). So it can be stated that the operational cost variable has a significant influence on the generation operation pattern. Meanwhile, for the economic factor variable, the value of tcount (3.161) > ttable (1.669), and the significance value is (0.000) < 0.05. This shows that economic factors (X2) have a significant and positive effect on generational operation patterns (Y). This shows that economic factors (X2) have a significant effect on generational operation patterns (Y). So it can be stated that economic factor variables have a significant influence on generational operation patterns. Simultaneous test results show that the value of Fcount (6.431) > FTable (3.14) is significant. (0.00) < 0.05, then the hypothesis is accepted. The regression model shows that the independent variables consist of operational cost variables (X1) and economic factor variables (X2), which together have a significant and positive effect on the dependent variable, namely the pattern of generation operations (Y). The adjusted R2 test results in this study obtained an adjusted R2 value of 0.513, which means that the magnitude of the influence of the operating cost variable (X1) and the economic factor variable (X2) on the pattern of generation operations is 51.3%, while the remaining 48.7% is influenced by other factors not included in this study. Keywords: Operational Costs, Economic Factors, and Patterns of Generation Operations